Meningkatnya Kinerja Perusahaan Konstruksi Sebagai Dampak Peran Dan Hubungan Yang Positip Antara Networking Capability Dengan Business Process Agility - Wesly Tumbur ML Tobing; Ahmad Zaenuri; Putri Pratiwi (Universitas Sains dan Teknologi Komputer, 2022)
Abstract : The purpose of this research is to examine the role of networking capability to improve company performance through the use of business process agility in construction companies in Java Island. The research method was carried out quantitatively by collecting data by distributing questionnaires through electronic forms and printed formats which were delivered directly to respondents where the respondents were the company's top management, such as directors, CEOs, company owners, and company commissioners who work for contractor companies on the island of Java. The sampling technique was carried out purposively based on the criteria of top management who had worked for at least five years in a contractor company in Java Island. Based on these criteria, there are 254 top management who have met these criteria. Data were analyzed using statistical software AMOS 22. The results showed that networking capability had a positive and significant effect on business process agility and company performance. Likewise, process business agility has a positive effect on firm performance.